Penerapan Asuhan Keperawatan Post Op Section Caesarea dalam Indikasi Preeklampsia Berat - Darmi Arda; Hartaty Hartaty (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Sectio Caesarea is a medical action needed to assist in childbirth that cannot be carried out normally due to maternal health problems or the condition of the fetus, which is a factor that causes severe preeclampsia. Aim; knowing the application of Post Op Sc nursing care in indications of severe preeclampsia. Methods: The method used in this research is descriptive, with a case study approach taken in the postpartum ward of a private hospital in Makassar City in June 2020. Data were obtained from the patient's mother, nurses, health team, progress notes, and health records. Results: showing pain is the main problem that arises in Post Op Section Caesarea patients. After nursing actions, pain can be resolved. Conclusion; that from pain management carried out with the patient's pain results can be overcome influenced by the provision of developed pain management